EDUKASI PERLINDUNGAN DATA PRIBADI DALAM PENGGUNAAN APLIKASI PINJAMAN ONLINE BAGI MASYARAKAT INDRAMAYU - Moody Rizqy Syailendra; Alicia Andromeda Sanyoto; Diana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The development of digital technology has encouraged the widespread use of online loan applications among the public. The ease of access to financial services offered by this digital platform has a positive impact on increasing financial inclusion, especially in rural areas. However, the high level of use is not balanced with adequate digital literacy and legal understanding, so that the public becomes vulnerable to misuse of personal data. This is especially true for illegal online loan services that often exploit user data for detrimental interests. Based on these problems, this community service activity was held with the aim of providing education about the importance of protecting personal data in the use of online loan applications. This activity is designed in the form of direct socialization, interactive training, and the distribution of educational materials that are easy for the general public to understand. The targets of the activity are residents in several villages in Indramayu Regency who are included in groups vulnerable to digital risks, such as housewives, students, and village officials. The material provided includes an understanding of the types of personal data that must be protected, how to recognize illegal online loan applications, and preventive steps to maintain data security when accessing digital services. Through this activity, it is hoped that there will be an increase in public understanding and awareness in maintaining the security of personal data and supporting the national digital literacy program. This program is also expected to be able to form a society that is more legally aware and responsive to the risks posed by digital technology. ABSTRAK Perkembangan teknologi digital telah mendorong maraknya penggunaan aplikasi pinjaman online di kalangan masyarakat. Kemudahan akses terhadap layanan keuangan yang ditawarkan oleh platform digital ini memberikan dampak positif dalam meningkatkan inklusi keuangan, terutama di wilayah pedesaan. Namun, tingginya tingkat penggunaan tersebut tidak diimbangi dengan literasi digital dan pemahaman hukum yang memadai, sehingga masyarakat menjadi rentan terhadap penyalahgunaan data pribadi. Hal ini terutama terjadi pada layanan pinjaman online ilegal yang kerap mengeksploitasi data pengguna untuk kepentingan yang merugikan. Berdasarkan permasalahan tersebut, kegiatan pengabdian kepada masyarakat ini diselenggarakan dengan tujuan memberikan edukasi tentang pentingnya perlindungan data pribadi dalam penggunaan aplikasi pinjaman online. Kegiatan ini dirancang dalam bentuk sosialisasi langsung, pelatihan interaktif, serta penyebaran materi edukatif yang mudah dipahami oleh masyarakat umum. Sasaran kegiatan adalah warga di beberapa desa di Kabupaten Indramayu yang termasuk dalam kelompok rentan terhadap risiko digital, seperti ibu rumah tangga, pelajar, dan perangkat desa. Materi yang diberikan mencakup pemahaman mengenai jenis-jenis data pribadi yang wajib dilindungi, cara mengenali aplikasi pinjaman online ilegal, serta langkah-langkah preventif untuk menjaga keamanan data saat mengakses layanan digital. Melalui kegiatan ini, diharapkan terjadi peningkatan pemahaman dan kesadaran masyarakat dalam menjaga keamanan data pribadi serta mendukung program literasi digital nasional. Program ini juga diharapkan mampu membentuk masyarakat yang lebih sadar hukum dan tanggap terhadap risiko yang ditimbulkan oleh teknologi digital.